Some thermal and tectonic models for crustal melting in continental collision zones - England, P; Thompson, A (1986)
Calculated geotherms and the pressure-temperature-time (PTt) paths followed by rocks during continental thickening episodes are interpreted with respect to the volumes of crustal melt that may be formed during orogenesis in the absence of heat transfer by mantle-derived melts. Particular attention is paid to a tectonic history that may characterize wider orogenic belts, such as are represented most obviously at present by Tibet. This comprises a period of crustal thickening, followed by an interval during which the crust is thinned by extensional strain, rather than by erosion. The amount of crustal melt produced depends strongly on the amount of water (free, and in hydrated minerals) contained in the lower crust. However, we may expect several (1-5) km 3 of crustal melt per km 2 of orogen if a crust of around average continental surface heat flux (60-70 mW m -2) is thickened by a factor of two. For the lower surface heat flux, partial melting of a sedimentary source would produce predominantly S-type granites and, with slightly higher geotherms, doubling of crustal thickness can lead to partial melting of amphibolites to give I-type granitic activity and calc-alkaline volcanism. © 1986 The Geological Society.